Sediment microbial communities rely on different dissolved organic matter sources along a Mediterranean river continuum. (26th May 2016) - Freixa, A.; Ejarque, E.; Crognale, S.; Amalfitano, S.; Fazi, S.; Butturini, A.; Romaní, A. M.
Abstract: Heterotrophic bacteria play a key role in the degradation of organic matter and carbon cycling in river sediments. These bacterial communities are directly influenced by environmental variables that differ spatially and temporally in rivers. Here, we studied the longitudinal patterns of sediment bacterial community composition and dissolved organic matter utilization under base flow and drought conditions in a Mediterranean river. Our results indicated that sediment microbial communities were affected by dissolved organic matter quality and origin along the river continuum. In headwaters the potential degradation of cellulose and hemicellulose was greater (i.e., higher β‐glucosidase and β‐xylosidase activities), suggesting higher microbial utilization of allochthonous detritus from terrestrial origin. Conversely, the accumulation and transport of more recalcitrant compounds (i.e., decrease in the recalcitrant index) became potentially relevant downstream. Furthermore, discharge fluctuations had clear effects on bacterial community composition and dissolved organic matter use. The hydrological fragmentation of the river continuum during drought period generated sediment microhabitats dominated by gamma and delta‐Proteobacteria, with a greater potential capacity to degrade a wide range of compounds, particularly nitrogen containing moieties. During base flow conditions, we observed a higher occurrence of alpha‐Proteobacteria and a greater potential use of more recalcitrant carbon compounds, mostly of terrestrial origin. Overall, our findings suggest an upstream‐downstream longitudinal transition of sediment microbial communities that rely on allochthonous to autochthonous dissolved organic matter, and a shift toward autochthonous dissolved organic matter reliance during drought.